1974
DOI: 10.1079/bjn19740104
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal absorption rates of glucose, glycine and glycylglycine in Zambian African adults with malnutrition

Abstract: I. Absorption rates of glucose (from a 200 mM solution), glycine (from a 100 mM solution), and glycylglycine (from a 50 mM solution) have been estimated in six Zambian African adults with clinical evidence of malnutrition. A double-lumen tube technique was used to determine absorption rates from a 300 mm section of jejunum in vivo.2. Two of the subjects had ileal tuberculosis and Kaposi's sarcoma respectively. A third probably had abdominal tuberculosis. Three of them had pellagra. Mean serum albumin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Low serum immunoglobulin (especially IgG) concentrations have been reported in that disease (Jarnum et al, 1968;Klipstein and Falaiye, 1969). Subclinical malnutrition was not excluded in the present study, but that has been shown to be associated with normal glucose, glycine, glycylglycine, and xylose absorption (Cook, 1974c).…”
Section: Discussionmentioning
confidence: 60%
“…Low serum immunoglobulin (especially IgG) concentrations have been reported in that disease (Jarnum et al, 1968;Klipstein and Falaiye, 1969). Subclinical malnutrition was not excluded in the present study, but that has been shown to be associated with normal glucose, glycine, glycylglycine, and xylose absorption (Cook, 1974c).…”
Section: Discussionmentioning
confidence: 60%